2020
DOI: 10.1038/s41594-020-0401-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structures of the ATP release channel pannexin 1

Abstract: The plasma membrane ATP release channel pannexin 1 has been implicated in numerous physiological and pathophysiological processes associated with purinergic signaling, including cancer progression, apoptotic cell clearance, inflammation, blood pressure regulation, oocyte development, epilepsy and neuropathic pain. Here, we present nearatomic resolution structures of Xenopus tropicalis and Homo sapiens PANX1 determined by cryo-electron microscopy that reveal a heptameric channel architecture. Compatible with AT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 58 publications
5
93
0
Order By: Relevance
“…In light of these prior findings, it could be valuable to determine whether, like tenofovir, remdesivir also impacts both PANX1 channel activity and possibly PANX1-associated inflammatory signaling in COVID-19. This work would be facilitated by the recent advances in our understanding of the PANX1 structure, including identification of key extracellular regulatory residues ( 16 , 39 ). Remdesivir’s effects on PANX1 channels are not known but would merit investigation in light of the blocking effect of the related drug, tenofovir, and the established role of PANX1 in inflammation and regulation of virus life cycles.…”
Section: Panx1 and Nucleotide Analog Antiviralsmentioning
confidence: 99%
“…In light of these prior findings, it could be valuable to determine whether, like tenofovir, remdesivir also impacts both PANX1 channel activity and possibly PANX1-associated inflammatory signaling in COVID-19. This work would be facilitated by the recent advances in our understanding of the PANX1 structure, including identification of key extracellular regulatory residues ( 16 , 39 ). Remdesivir’s effects on PANX1 channels are not known but would merit investigation in light of the blocking effect of the related drug, tenofovir, and the established role of PANX1 in inflammation and regulation of virus life cycles.…”
Section: Panx1 and Nucleotide Analog Antiviralsmentioning
confidence: 99%
“…PANX1 belongs to the innexin/pannexin superfamily and forms a heptameric pore in the plasma membrane ( Deng et al, 2020 ; Michalski et al, 2020 ; Qu et al, 2020 ), functioning as a large-pore channel capable of passing small molecules ( Bao et al, 2004 ; Dahl and Muller, 2014 ; Panchin et al, 2000 ; Penuela et al, 2013 ). It has been reported that apoptotic cells release ATP, AMP, and also UTP through the PANX1 channel as ‘find-me’ signals to attract macrophages and that the PANX1 channel is opened by caspase-3/7, which cleaves the C-terminal region of the channel ( Chekeni et al, 2010 ; Elliott et al, 2009 ; Yamaguchi et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…PANX1 belongs to the innexin/pannexin superfamily and forms a heptameric pore in the plasma membrane (Deng et al, 2020; Michalski et al, 2020; Qu et al, 2020), functioning as a large-pore channel capable of passing small molecules (Bao et al, 2004; Dahl and Muller, 2014; Panchin et al, 2000; Penuela et al, 2013). It has been reported that apoptotic cells release ATP, AMP, and also UTP through the PANX1 channel as “find-me” signals to attract macrophages and that the PANX1 channel is opened by caspase-3/7, which cleaves the C-terminal region of the channel (Chekeni et al, 2010; Elliott et al, 2009; Yamaguchi et al, 2014).…”
Section: Resultsmentioning
confidence: 99%